Two Test Assembly Methods With Two Statistical Targets - Huijing, Zheng; Junjie, Li; Pingfei, Zeng; Chunhua, Kang (Frontiers in Psychology, 2022)
In educational measurement, exploring the method of generating multiple high-quality parallel tests has become a research hotspot. One purpose of this research is to construct parallel forms item by item according to a seed test, using two proposed item selection heuristic methods (minimum parameters-information-distance method [MPID] and minimum information-parameters-distance method [MIPD]). Moreover, previous research addressing test assembly issues has been limited mainly to situations in which the information curve of the item pool or seed test has a normal or skewed distribution. However, in practice, the distributions of information curves for tests are diverse. These include multimodal distributions, the most common type of which is the bimodal distribution. Therefore, another main aim of this article is to extend the information curves of unimodal distributions to bimodal distributions. Thus, this study adopts simulation research to compare the results of two IRT-based item matching methods (MPID and MIPD) using different information curve distributions for item pools or seed tests. The results show that the MPID and MIPD methods yield rather good performance in terms of both two statistical targets when the information curve has a unimodal distribution and two new methods yield better performance than two existing methods in terms of test information functions target when the information curve has a bimodal distribution.